Mapping the Evaluation Landscape: A Systematic Review of Research Design, Instruments, and Methods in Public Policy Implementation Studies - Daeng Baji, Intan Suciati; Pramono, Sidik (Jurnal Locus Penelitian dan Pengabdian, 2025)
The need for evidence-based evaluation of public policy implementation is increasingly urgent amid the complexity of contemporary governance and demands for accountability. This study aims to identify and analyse the characteristics of public policy implementation evaluation research through a systematic literature review (SLR) approach. By analysing 119 articles from Scopus-indexed journals, this study maps six main dimensions: publication trends, research design, evaluation topics, evaluation approaches, data collection instruments, and data analysis techniques. Findings reveal a dominance of qualitative approaches, particularly thematic analysis and the use of interviews, as well as a concentration of topics in the health, education, and social welfare sectors. The study also highlights limitations in the use of advanced quantitative methods and the need to strengthen cross-sectoral evaluative instruments. The implications of this research underscore the urgency of enhancing evaluative capacity, diversifying methodological approaches, and institutionalizing evaluation within the policy cycle to strengthen adaptive and sustainable public governance.